Analisis Tantangan dan Peluang Kebijakan PTN-BH: Studi Kebijakan Pendidikan Tinggi di Indonesia - Ainur Rosyida, Fatia; Sa'diyah, Zumrotus; Suti'ah; Aziz, Abdul (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Currently, funding and financing issues are still the main challenges for higher education institutions. Universities have problems in obtaining funds to finance operational activities. Therefore, through the determination of Universities as PTN-BH by the government, it can provide freedom in managing financing. This study aims to examine the challenges and opportunities of PTN-BH policies in Indonesia. This research method uses library study research. The research data was collected based on reference sources from books, journals, articles, and official websites that are appropriate to the topic of discussion. The analysis of this research data uses the type of content analysis to describe the content of the research relevantly. The results of the study stated that the impact of PTN-BH policies on campus funding is to increase income, funding sources do not depend on the APBN, and can manage finances independently. The impact of PTN-BH policies on institutional performance is that they can improve the quality of education, and improve research performance by expanding cooperation with other institutions. The challenges of PTN-BH policies in Indonesia include: the government will reduce PTN subsidy funds, increase tuition fees, adequacy of facilities, international competitiveness, and quality graduate profiles. Meanwhile, the opportunities consist of several types, namely providing flexibility in managing financing, making PTN more flexible in responding to changes, helping PTN develop through cooperation with all parties, encouraging PTN as a center for superior innovation and research, and PTN can manage human resources and educational staff.